1995
DOI: 10.1071/sr9950525
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-cycle processes and acidification of soils in grazed pastures receiving or not receiving excreta for 23 years

Abstract: Soil acidification in agricultural systems can be related to production and consumption of protons during nutrient cycling processes. Carbon and nitrogen cycles are particularly important in this respect for grazed pastures. Rates of acidification were calculated for grazed pastures that had received animal exreta in the normal way and for areas that had been free from excreta for 23 years. Acidification rates were 3.59 and 0.86 kmol H+ ha-1 yr-1 respectively. Measurement indicated that the areas were not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…Sinclair et al (1993) suggested that where it is not financially viable to lime hillcountry, long-term sustainability of farming is questionable. Despite this, there is no clear evidence for acidification of soils in legume-based pastures in New Zealand (Carran & Theobold 1995). Sakadevan et al (1993) measured only small annual NO3-N leaching losses (1.3 to 3.7 kg N ha" 1 ) within the trial described here.…”
Section: Soilphmentioning
confidence: 72%
See 1 more Smart Citation
“…Sinclair et al (1993) suggested that where it is not financially viable to lime hillcountry, long-term sustainability of farming is questionable. Despite this, there is no clear evidence for acidification of soils in legume-based pastures in New Zealand (Carran & Theobold 1995). Sakadevan et al (1993) measured only small annual NO3-N leaching losses (1.3 to 3.7 kg N ha" 1 ) within the trial described here.…”
Section: Soilphmentioning
confidence: 72%
“…The effect of intensification on soils and pastures was generally viewed as being beneficial, resulting in increases in soil organic matter quantity and quality (Haynes & Williams 1993), although some negative consequences were quantified, e.g., the effects of soil slip erosion on pastures and soils (Trustrum et al 1984) and the influence of intensification on nutrient and soil losses (Lambert et al 1985). More recently, the potential for soil acidification has been debated (Bolan et al 1991;Carran & Theobold 1995).…”
Section: Introductionmentioning
confidence: 99%
“…(2) where DMin is the dry matter intake (kg/SU), CC Monaghan et al (1996) Monaghan et al (1996) Monaghan et al (1996) Monaghan et al (1996) Sinclair (1995) Carran & Theobald (1995) a In mg NO3" -N per kg soil. b When an additional 150 kg MCP-P was applied, the EC contents were 0.64, 0.54, 0.47, and 0.42 mol c /kg DM for the 4 N rates, respectively.…”
Section: )mentioning
confidence: 99%
“…Dry matter production estimates from the Aorangi site were approximately 6 and 15 tonnes DM/ha per year from fence-line and paddock plots, respectively (Carran & Theobald 1995). Net differences in DM and excreta returns between sites of over 200 kg K/ ha per year was considered a reasonable assumption with total net K removal from fence-line locations at the Aorangi site over the last 23 years estimated at c. 6000 kg K/ha or c. 260 kg K/ha per year.…”
Section: North Otago Trialsmentioning
confidence: 99%